Grain legumes of the lowland tropics - Rachie, K.O.; Roberts, L.M. (Elsevier, 1974)
This chapter discusses four species of grain legumes of the lowland tropics—that is, peanuts, pigeon peas, cowpeas, and mung beans. Various aspects of these species, such as plant improvement, plant protection, growth processes, and management are described. These four species made up 87% of both the cultivated area and total production on a worldwide basis. Some botanical and adaptive characters of tropical lowland grain legumes are summarized to facilitate direct comparisons of their potential for specific situations. Although species are grouped according to their presumed ecological use patterns, considerable overlap occurs in adaptation and in microclimates of particular locales within regions. The chapter describes various comparative features of tropical species, such as (1) plant types, (2) soil and climate preference, (3) susceptibility to pests and diseases, and (4) yielding ability. To emphasize the positive aspects of growing tropical legumes, a broad array of uses for these crops and their beneficial effects on soil and crops are summarized.